Parametric crystal optics of nonmagnetic ferroics - Vlokh, O.G. (Condensed Matter Physics, 1998)
Proceeding from the symmetry principles of crystal physics and thermodynamics
we analyze parametrical optical phenomena induced by external
fields of different kind and structural phase transitions in ferroelectrics and
ferroelastics. Special attention is paid to the phenomena of spatial dispersion
(electro- and piezogyration). A phenomenological approach to the description
of these phenomena is illustrated by the most expressive experimental
results obtained for the following crystals: KH₂₍₁₋x₎ D₂x PO₄ (KDP,
DKDP), K₂H₂AsO₄ (CDA), RbH₂PO₄ (RDP), Pb₅(Ge₍₁₋x₎ Six)₃ O₁₁,
Pb₃ (PO₄ )₂ , K₂ Cd₂ (SO₄ )₃ , (NH₃ CH₂ COOH)₃H₂ SO₄ (TGS), and
NaKC₄H₄O₆ 4H₂O (RS). Apart from new effects in the crystals of the
A₂BX₄ group with incommensurately modulated structure, in particular,
crystals [N(CH₃)₄]₂ ZnCl₄ , [N(CH₃)₄ ]₂ FeCl₄ , K₂ ZnCl₄ , K₂ ZnCl₄ ,
Co²⁺ are considered. Виходячи з симетрійних принципів кристалофізики і термодинаміки, проведено аналіз параметричних оптичних явищ, індукованих зовнішніми полями різного типу, структурними фазовими переходами в
сегнетоелектриках і сегнетоеластиках. Особлива увага звертається на явища просторової дисперсії (електро- і п’єзогірація).Феномено-логічний підхід до опису цих явищ ілюструється найбільш виразними експериментальними результатами, одержаними для кристалів:KH₂₍₁₋x₎ D₂x PO₄ (KDP, DKDP), K₂H₂AsO₄ (CDA), RbH₂PO₄ (RDP), Pb₅(Ge₍₁₋x₎ Six)₃ O₁₁, Pb₃ (PO₄ )₂ , K₂ Cd₂ (SO₄ )₃ , а також для (NH₃ CH₂ COOH)₃H₂ SO₄ (TGS), NaKC₄H₄O₆ 4H₂O (RS). Окремо розглядаються нові ефекти в кристалах групи A₂Bx₄ неспівмірно модульованоюструктурою, зокрема у кристалах [N(CH₃)₄]₂ ZnCl₄ , [N(CH₃)₄ ]₂ FeCl₄ , K₂ ZnCl₄ , K₂ ZnCl₄ ,
Co²⁺.